What are the experiences of nurses working during the Covid-19 pandemic, and how were they supported? : a case study of two countries (Israel and New Zealand) : thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy, Massey University, School of Nursing - Paletova, Martina (Massey University, 2023)
The Covid-19 pandemic and all its associated stressors had a significant negative impact on the emotional and physical capacity of nurses. Now, as the pandemic ends, nurses are leaving the profession in droves, burnout being the suggested reason. This study examines the experiences of nurses in regard to the support they received during the Covid-19 pandemic. The theoretical framework chosen for this study was Critical Social Theory because it examines the power dynamics and structural factors that shaped nurses’ responses and their capacity to care. The methodology for this work was Critical Discourse Analysis, underpinned by a Foucauldian lens as it allows for a critique of how power relations and discourses shaped knowledge, practices, and subjectivities of nurses and their practice. A case study of nurses from two countries (Israel and New Zealand), was used to examine the discourses of the pandemic across public, organisational and operational levels of health care. Methods included interviews, a content analysis of texts, and archaeology/ genealogy of the pandemic. As my personal journey is integral to the study, I have also integrated an autoethnographic approach as its captures my firsthand experiences to provide rich, contextual data to support and inform the nursing perspective. The nurses working in health care in the pandemic years describe struggles with illogical rules, confusing information, lack of personal protection, and questions about principles and ethics, in contrast with the natural and professional commitment to care for the patient. In conclusion, rather than burnout due to Covid-19 pandemic, the concept of ‘moral injury’ due to systemic pressure more accurately reflects the ongoing crisis in the nursing profession. This issue cannot be solved through resilience training or special wellness programs, as advocated by some professionals. Instead, a need for a systematic change is argued.
Keywords: nurse, nursing, Covid-19, pandemic, New Zealand, Israel, moral injury; 420505 Nursing workforce; 420207 Major global burdens of disease